Production Test of 5 Watermelon Variety Candidates (Citrullus Lanatus (Thunb.) Matsum. & Nakai) F1 Hybrida Result of Assembly Against 4 Comparing Varieties - Romadhani, Ikrom Tri Cahya Putra; Septia, Erfan Dani; Mursiani, Sri (Universitas Muhammadiyah Malang, 2023)
Watermelon (Citrullus lanatus) is a widely consumed and cultivated fruit in Indonesia, cherished for its numerous benefits, high economic value, and short plant life. To enhance watermelon quality, plant breeding is employed, aiming to develop superior hybrid varieties. This study, conducted between September and November 2022 on PT. Aditya Sentana Agro's experimental land, evaluated candidate hybrid watermelon varieties (codes 3078, 3079, 3080, 2844, 2845) against comparison varieties (Winda, Mardi, Black Panther, Palguna). Using Randomized Complete Block Design (RCBD) with one genetic factor at 9 levels, repeated 3 times, a total of 27 experimental units were established, each consisting of 10 plants, summing up to 270 plants. Qualitative variables such as fruit skin color, pattern color, flesh color, and shape, along with quantitative variables like fruit weight, length, diameter, dissolved solids, flowering day, skin thickness, and percentage of fruit damage, were observed. The research revealed variations in fruit weight, length, diameter, dissolved solids, and flowering day among the different varieties. Promising candidates for new varieties were identified as codes 2845 and 3078 based on these quantitative traits. This study contributes valuable insights into the potential advancements in watermelon breeding, emphasizing the importance of selecting varieties with desirable characteristics for improved agricultural outcomes.